Latining America : Black-Brown Passages and the Coloring of Latino/a Studies - Milian, Claudia (Book collections on Project MUSE., 2013)
With this book, the author proposes that the economies of blackness, brownness, and dark brownness summon a new grammar for Latino/a studies that she names "Latinities." The author's innovative study argues that this ensnared economy of meaning startles the typical reading practices deployed for brown Latino/a embodiment. This book keeps company with and challenges existent models of Latinidad, demanding a distinct paradigm that puts into question what is understood as Latino and Latina.